2016
DOI: 10.1111/evo.12938
|View full text |Cite
|
Sign up to set email alerts
|

Selection on an antagonistic behavioral trait can drive rapid genital coevolution in the burying beetle, Nicrophorus vespilloides

Abstract: Male and female genital morphology varies widely across many taxa, and even among populations. Disentangling potential sources of selection on genital morphology is problematic because each sex is predicted to respond to adaptations in the other due to reproductive conflicts of interest. To test how variation in this sexual conflict trait relates to variation in genital morphology we used our previously developed artificial selection lines for high and low repeated mating rates. We selected for high and low re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Sexual selection has generally been considered to be a positive diversifying force driving the evolution of genitalia and increases in the rate of speciation (Darwin 1871;Panhuis et al 2001;Hosken & Stockley 2004). Recent studies have contributed to our understanding of divergence and coevolution in animal genitalia (Eberhard 2010;Masly 2012;Hopwood et al 2016), but most of those works have lacked data on female genitalia (Eberhard 1985(Eberhard , 2004. However, the exact mechanisms that have promoted the rapid genital divergence in many groups (including the freshwater crabs) remain debatable and are still mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual selection has generally been considered to be a positive diversifying force driving the evolution of genitalia and increases in the rate of speciation (Darwin 1871;Panhuis et al 2001;Hosken & Stockley 2004). Recent studies have contributed to our understanding of divergence and coevolution in animal genitalia (Eberhard 2010;Masly 2012;Hopwood et al 2016), but most of those works have lacked data on female genitalia (Eberhard 1985(Eberhard , 2004. However, the exact mechanisms that have promoted the rapid genital divergence in many groups (including the freshwater crabs) remain debatable and are still mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies that have reported on female genital shape variation have utilized two‐dimensional (2D) geometric morphometric techniques (Evans, van Lieshout, & Gasparini, ; Hopwood et al., ; Orbach et al., ; Polihronakis, ; Simmons & García‐González, ). However, with the increase in the accessibility of three‐dimensional (3D) scanning technologies and analysis software, more studies are beginning to utilize 3D techniques to capture a level of variation that is not possible with 2D methods (Semple, Peakall, & Tatarnic, ; Tatsuta, Takahashi, & Sakamaki, ).…”
Section: Where To Next For the Study Of Female Genitalia?mentioning
confidence: 99%
“…Using artificial selection lines on the burying beetle, Nicrophorus vespilloides , Hopwood et al. () selected for high or low mating rate finding that after only 10 generations, the genital morphology of beetles in the lines selected for high and low mating rates had diverged relative to control lines. Furthermore, male and female genitalia were found to coevolve within selection lines.…”
Section: Where To Next For the Study Of Female Genitalia?mentioning
confidence: 99%
“…Genital shape, rather than size, is often used by taxonomists as a means of distinguishing between closely related species [58,59], implying greater divergence in genitalic shape than size [22]. Indeed, numerous experimental evolution studies have found direct evidence for sexual selection acting on genital shape across a range of taxa [23,60,61].…”
Section: Genital Shape Complexitymentioning
confidence: 99%
“…There is therefore considerable interest in developing automated methods capable of quantifying shape across such complex and diverse structures as animal genitalia. In some instances, traditional landmark-based GMM techniques have been applied [60,[62][63][64][65]. Such studies frequently consider genital shape variation intraspecifically, or between morphologically similar sister taxa [66,67].…”
Section: Genital Shape Complexitymentioning
confidence: 99%